Symbiotic Anthropology and Politics in a Postmodern Age: Rethinking the Political Philosophy of Johannes Althusius (1557–1638) - Vorster, Nico (Renaissance and Reformation / Renaissance et Réforme, 2015)
Postmodern societies are increasingly characterized by a hyperpluralism that coincides with an interdependence between social spheres and structures. Actions in one sphere of life often impinge on other spheres of life. This leads to a consistent and endemic conflict between the social dynamics of plurality and the need for social unity. The symbiotic political theory of Johannes Althusius (1557–1638), which attempts to preserve unity through organized plurality, might be helpful in addressing the plurality/unity conundrum so characteristic of postmodern societies. Central to this approach are the anthropological and political notions of symbiosis, association, communication, and sharing. After providing some background to Althusius’s thought, this article discusses his symbiotic anthropology and explicates his symbiotic political theory. The article concludes by identifying five features of Althusius’s political theory that might be helpful to contemporary postmodern society.